2021
DOI: 10.34172/ps.2021.11
|View full text |Cite
|
Sign up to set email alerts
|

Natural products as inhibitors of COVID-19 main protease–A virtual screening by molecular docking

Abstract: Background: The novel coronavirus (2019-nCoV) causes a severe respiratory illness unknown to a human before. Its alarmingly quick transmission to many countries across the world has resulted in a global health emergency. Therefore, an imminent need for drugs to combat this disease has been increased. Worldwide collaborative efforts from scientists are underway to determine a therapy to treat COVID-19 infections and reduce mortality rates. Since herbal medicines and purified natural products have been reported … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The glycosylation of kaempferol at C3 also showed an improved effect on its antiviral activity [24] which is related to the finding of this study for improving the binding affinity with M pro by glycosylation at C-3. Another in silico study also revealed the glycosylation of C-7 improves the binding affinity of flavone with COVID-19 M pro [25]. To further evaluate the potency of tested compounds as inhibitors of covid-19, the commercially available anti-HIV ritonavir which was approved by FDA as the covid-19 drug was also docked to the molecule to the protein.…”
Section: Molecular Docking Resultsmentioning
confidence: 99%
“…The glycosylation of kaempferol at C3 also showed an improved effect on its antiviral activity [24] which is related to the finding of this study for improving the binding affinity with M pro by glycosylation at C-3. Another in silico study also revealed the glycosylation of C-7 improves the binding affinity of flavone with COVID-19 M pro [25]. To further evaluate the potency of tested compounds as inhibitors of covid-19, the commercially available anti-HIV ritonavir which was approved by FDA as the covid-19 drug was also docked to the molecule to the protein.…”
Section: Molecular Docking Resultsmentioning
confidence: 99%